Sosialisasi dan Pelatihan Tata Cara Pendaftaran Hak Atas Tanah pada Kampung Buti - Alputila, Marlyn Jane; Mote, Hery H Fernando (Yayasan Kawanad, 2023)
Land has a very important value due to its nature and fact. Land, by its very nature, is immutable and fixed, making it a promising investment value for most people. This is because land prices or sales prices tend to continue to rise. Kampung Buti generally do not understand the importance of owning land certificates and many people still believe that the cost of issuing these certificates is high. Most of the proofs are in the form of Kikitir or SPPT (they consider proof of ownership of property). The rest are in the form of sales agreements (AJBs), but very few are in the form of title deeds. Result of this activity: (1) Journal, (2) Land Title Registration Procedures and Conditions, (3) Land Title Registration Paperback. Methodologies used in aid programs are implemented through seminars, workshops, and guidance in the preparation of the I-Kind Anti-Corruption Program. This includes developing training materials for caregiver lectures, case studies, group discussions, games, and brainstorming. This mentoring activity was carried out in three phases: the seminar in the first phase, her in the second phase. Third phase of workshops and technical guidance, and support and training for land title registration. It is hoped that this service will raise awareness of the importance of land title registration.